1999
DOI: 10.1136/ip.5.1.78-b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a poison prevention lesson for kindergarten and third grade students

Abstract: Objectives-The purpose of this study was to evaluate the MORE HEALTH poison prevention lesson that is given to kindergarten and third grade students in Hillsborough County, Florida. The lesson reaches approximately 6000 students per year. Methods-The evaluation was based on a post-test only control group design. Three schools were chosen as evaluation sites and three served as control settings. Students were administered a previously tested, age appropriate questionnaire that addressed the goals of the poison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…25,27,29,32 These studies show that parents report storing poisonous substances out of children's reach in 18% to >90% of households. [23][24][25][26][27][28][29][30][31][32] The percentage of households in which poisons were reportedly kept locked also varied widely, ranging from 9% to 89%. 26,27 The variations in reported poison storage practices are likely explained by the regional, economic, and cultural differences of the populations studied as well as by variations across studies in self-report versus observed storage.…”
Section: Introductionmentioning
confidence: 99%
“…25,27,29,32 These studies show that parents report storing poisonous substances out of children's reach in 18% to >90% of households. [23][24][25][26][27][28][29][30][31][32] The percentage of households in which poisons were reportedly kept locked also varied widely, ranging from 9% to 89%. 26,27 The variations in reported poison storage practices are likely explained by the regional, economic, and cultural differences of the populations studied as well as by variations across studies in self-report versus observed storage.…”
Section: Introductionmentioning
confidence: 99%
“…This project has been funded by England's NHS Executive National R&D Programme in Mother and Child Health (CH [10][11][12][13][14][15][16][17][18][19][20][21].…”
mentioning
confidence: 99%
“…There is a wide range of strategies for preventing poisoning including child-resistant packaging,14 locks on cabinets or drawers, storage out of reach, not transferring substances from original containers, replacing in the usual storage place immediately after use,15 safely disposing of unwanted medicines,15 using substances containing bittering agents,16 educating children about the dangers of substances,17 using poison control centres (PCCs),15 18 and, in some countries, emetics have been used to induce vomiting after a poisoning 19…”
mentioning
confidence: 99%